Revealing the Message of Manuscript Writing: A Narrative Study of the Peksi Bayan Fairy Tale (Pakualaman) - Rahmat Rahmat; Nirbito Hanggoro Pribadi; Djoko Sulaksono; Rahmat Setiawan Saefullah (Universitas 17 Agustus 1945 Surabaya, 2026)
The Peksi Bayan text is a fairy tale text from the written tradition produced by Pakualaman in the 19th century. The text volume is relatively short (one canto) but was written repeatedly in five manuscripts, this shows a uniqueness because the main corpus, the Bayan Budiman text, is told at length in the form of a frame story. With the presence of copies of the Peksi Bayan text, this research focuses on revealing the message of the writing of the text. The theories used are philology and narrative structure. Philology is used to approach the text written in Javanese language and script, while the narrative structure used is the Tzvetan Todorov model which aims to reveal the meaning of verbal, syntactic, and semantic aspects. The results are text edits and translations as well as the message of the writing of the text, namely the hope of the Pakualaman dynasty for its young generation to have the main character in the field of leadership (learning to listen and consider suggestions) and as objects of leadership (to carry out and obey orders). Practically, the results of this research can be used as reading material or learning materials in schools.